Respuesta :

Answer:

1

Step-by-step explanation:

To evaluate, substitute x = - [tex]\frac{2}{3}[/tex] into f(x), that is

f(- [tex]\frac{2}{3}[/tex] )

= 3(- [tex]\frac{2}{3}[/tex] )² + 2(- [tex]\frac{2}{3}[/tex] ) + 1

= 3([tex]\frac{4}{9}[/tex] ) - [tex]\frac{4}{3}[/tex] + 1

= [tex]\frac{4}{3}[/tex] - [tex]\frac{4}{3}[/tex] + 1

= 0 + 1

= 1

Answer:

1

Step-by-step explanation:

f(x) = 3x² + 2x + 1

f(-2/3) = 3x² + 2x +1

f(-2/3) = 3(-2/3)² + 2(-2/3) + 1          

Substitute the value in for all the x's

f(-2/3) = 3(4/9) + 2(-2/3) + 1

f(-2/3) = 12/9 + (-4/3) + 1

f(-2/3) = 4/3 + (-4/3) + 1                

Subtracting 4/3 by (-4/3) gets you 0 so I didn't write it down.

f(-2/3) = 1

So, the answer I got is 1

ACCESS MORE